2020
DOI: 10.5964/meth.2817
|View full text |Cite
|
Sign up to set email alerts
|

Modeling heterogeneity of the level-1 error covariance matrix in multilevel models for single-case data

Abstract: Previous research applying multilevel models to single-case data has made a critical assumption that the level-1 error covariance matrix is constant across all participants. However, the level-1 error covariance matrix may differ across participants and ignoring these differences can have an impact on estimation and inferences. Despite the importance of this issue, the effects of modeling between-case variation in the level-1 error structure had not yet been systematically studied. The purpose of this simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
(46 reference statements)
1
9
0
Order By: Relevance
“…Although the REML approach generally performs well with SCED data, it was found that a non-convergence issue could be encountered when analyzing complex multilevel models of SCED data (Baek & Ferron, 2020). Complex models typically involve more parameters, which can be computationally intensive and lead to a non-convergence issue.…”
Section: Advanced Modeling Optionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the REML approach generally performs well with SCED data, it was found that a non-convergence issue could be encountered when analyzing complex multilevel models of SCED data (Baek & Ferron, 2020). Complex models typically involve more parameters, which can be computationally intensive and lead to a non-convergence issue.…”
Section: Advanced Modeling Optionsmentioning
confidence: 99%
“…On top of providing a feasible option to solve the non-convergence issue, the Bayesian estimation offers other potential benefits when applied with noninformative and weakly informative priors. Several studies have indicated that the Bayesian estimation can produce precise variance component estimation in a certain condition, more accurate effect size estimation for nonlinear SCED data in comparison to the likelihood estimation (Baek & Ferron, 2020; Baek et al, 2020a; Joo & Ferron, 2019; Moeyaert et al, 2017; Rindskopf, 2014a, 2014b; Shadish et al, 2013; Swaminathan et al, 2014). Therefore, the Bayesian approach can be a practical alternative for researchers who use multilevel models with SCED data, particularly for those estimating a complex model.…”
Section: Advanced Modeling Optionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, these techniques are not common ly used in meta-analyses (Jamshidi et al, 2022;Natesan, 2019), probably because they are not well understood by practitioners. Specifically, using multilevel models requires making several complex modeling decisions that may have an impact on the validity of the estimates (Baek & Ferron, 2020;Moeyaert et al, 2016). Moreover, such top-down techniques may not align well with the dominant visual analytical approach, and reduce a large amount of raw data to a single omnibus effect size (Barbosa Mendes et al, 2022) that may not thoroughly capture the complexity of the data (Parker & Vannest, 2012).…”
Section: Top-down Versus Bottom-up Meta-analysis Of Scedsmentioning
confidence: 99%